Pengembangan Sistem Kenaikan Pangkat dan Jabatan Dosen Fakultas Ilmu Komputer Universitas Brawijaya - Muhammad Safreza; Denny Sagita Rusdianto; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The functional position of the lecturer is the position of the lecturer based on the , responsibilities, duties, rights and authority in Higher Education based on certain expertise and individual nature. While rank is a position that shows the level of an employee based on his position in a series of staffing and is used as a base for payroll. In the Faculty of Computer Science, Universitas Brawijaya (FILKOM) from the field findings of several FILKOM lecturers that the lecturer had many activities. Then when the file validation and verification process in the FILKOM employee proposed a frequent error so that it did not have time to process further revisions in collecting files in 4 fields and administrative files for proposed promotions and / or functional positions. Coupled with the lecturer still doing the AK calculation manually by looking at the guide so that it allows even fatal calculation errors can be mistaken in the calculation of AK in each activity. In this study aims to help FILKOM lecturers in collecting 4 fields of files, assisting in the validation and verification of 4 fields of files, monitoring the status of proposals, and also assisting lecturers in calculating AK lecturers' activities automatically based on AK assessment guidelines. In this study using a prototyping approach. And in its implementation, it applies dummy webservice to retrieve BKD file data, Universitas Brawijaya staff and lecturers, especially FILKOM. The results of this study were obtained twenty-eight functional requirements and one non-functional requirement obtained from 1 prototyping iteration process. From the results of unit testing, integration and compatibility testing of the browser environment, the results are 100% valid.